Wild Edible Plants of Pertek (Tunceli-Turkey) - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2015)
An ethnobotanical study was carried out in Pertek (Tunceli, Turkey) between April 2009-June 2012. For this purpose, the center of Pertek and all of the 45 villages were visited. During the field works, 627 plant specimens were collected and various ethnobotanical information regarding these plants was classified. In this paper which is a part of ethnobotanical study, wild edible plants of Pertek are presented. This investigation revealed that 109 taxa belonging to 30 families are being used by local people for nutrition. The plants were mostly used as food (73 taxa), beverage (30 taxa) and spice (12 taxa). This study is the first comprehensive survey of ethnobotanical aspects of Pertek region and all taxa presented in this paper are recorded as food for the first time in Pertek. All of the 73 plants utilized as food in Tunceli and 3 taxa of them in Turkey are recorded for the first time.
Keywords: Ethnobotany; Wild Edible Plants; Pertek; Tunceli; Turkey